Edukasi Kesiapan Menarche Dan Pubertas Di SDN Ngadas 01 Desa Ngadas Kec. Poncokusumo Kab. Malang - Shinta Wahyusari; Apriyani Puji Hastuti; Widia Shofa Ilmiah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Every teenage girl will experience menstruation. The problem that often arises is the negative attitude shown when experiencing their first menstruation or menarche which is caused by a lack of knowledge. Education with appropriate methods and use of media is carried out to increase the understanding of menarche and skills in maintaining personal hygiene during menstruation. This service activity was carried out at SDN 01 Ngadas which was attended by 20 students from class III to class VI. The activities carried out were in the form of providing education using audiovisual. The method used is lecture, discussion, quiz and simulation.The results showed that there was an increase in participants' knowledge and skills to maintain personal hygiene during menstruation.